Propriedade Microestrutural do Refinamento da Liga Amorfa Al54Nb45B7 - Nascimento, Luciano; Melnyk, Anastasiia; Jamshidi, Lourdes Cristina L. A.; Rodbari, Reza Jamshidi (Orbital: The Electronic Journal of Chemistry, 2016)
The presence of niobium in the alloy creates regions of intermetallic phases contained in Al54Nb45B7 amorphous alloy which becomes a potent heterogeneous nucleation on the substrate for nucleation with dendritic presence of aluminum oxides due to diffusive processes on the surface of the amorphous alloy Al54Nb45B7. This alloy is extremely low cost, but with applications in many sectors of the chemical and petrochemical industry in emphasis because its mechanical deformation is high due to the presence of (Nb or B) in the aluminum acting mainly as grain refiners to improve their mechanical and thermal properties by using the mechanical alloying. The combined use of Niobium and Boron (intermetallic phases are formed by adding powder of Al and Nb), instead of Niobium or Boron, individually, is a highly effective way to refine the grain size of alloy Al Nb-B in their microstructure without causing inconvenience in your network for unwanted deformations. To that end the present study compared the effect of grain refining promoted by the addition of niobium and the addition of Boron in Al54Nb45B5 obtained by high energy mill under argon atmosphere and analyzed by diffraction of X rays (XRD), scanning electron microscopy and Energy Dispersive (SEM / EDS).DOI: http://dx.doi.org/10.17807/orbital.v8i3.808